2022
DOI: 10.47717/turkjsurg.2022.5406
|View full text |Cite
|
Sign up to set email alerts
|

Demographic factors associated with length of stay in hospital and histological diagnosis in adults undergoing appendicectomy

Abstract: Objective: Appendicectomy remains of the most common emergency operations in the United Kingdom. The exact etiologies of appendicitis remain unclear with only potential causes suggested in the literature. Social deprivation and ethnicity have both been demonstrated to influence outcomes following many operations. There are currently no studies evaluating their roles with regards to severity and outcomes following appendicectomy. Material and Methods: Demographic data were retrieved from hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In this study, the gender affected significantly the hospital stay, where females tended to spend more days than males (p = 0.003). On the difference, Alharbi et al [ 1 ] and Bhanderi et al [ 17 ] found that males spent more days than females (p = 0.011 and 0.029, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the gender affected significantly the hospital stay, where females tended to spend more days than males (p = 0.003). On the difference, Alharbi et al [ 1 ] and Bhanderi et al [ 17 ] found that males spent more days than females (p = 0.011 and 0.029, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[1] and Bhanderi et al [17] found that males spent more days than females (p = 0.011 and 0.029, respectively).…”
Section: Discussionmentioning
confidence: 99%